Uwagi etymologiczne w dawnych tekstach użytkowych (na przykładzie Kroniki, to jest historyi świata Marcina Bielskiego, Informacyi matematycznej Wojciecha Bystrzonowskiego i Nowych Aten Benedykta Chmielowskiego) - Kozaryn, Dorota; Szczaus , Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The subject of the analysis in the article are the etymological explanations presented in the old non-literary texts (i.e. the texts that function primarily outside literature, serving various practical purposes), i.e. in the sixteenth-century Kronika, to jest historyja świata (Chronicle, that is the history of the entire world) by Marcin Bielski and in two eighteenth-century encyclopaedic texts: Informacyja matematyczna (Mathematical information) by Wojciech Bystrzonowski and Nowe Ateny (New Athens) by Benedykt Chmielowski. The review of the etymological comments allows us to take notice of their considerable substantive and formal diversity. These comments apply to both native and foreign vocabulary. On the one hand, they provide information on the origin of proper names (toponyms and anthroponyms), and on the other hand, a whole range of these etymological comments concern common names. A depth of etymological comments presented in non-literary texts is significantly diversified and independent of the nature of the vocabulary to which these comments apply – they can be merely tips on sources of borrowings of foreign words, but they can also constitute a deeper analysis of the meaning and structure of individual words, both native and foreign. These comments are usually implementations of folk etymology. The role of etymological considerations in former non-literary texts is significant. First of all, these texts have a ludic function, typical of popularised texts – they are supposed to surprise, intrigue and entertain readers. Secondly, they serve a cognitive function typical of non-literary texts – they are supposed to expand the readers’ knowledge about the world and language. Thirdly, they have a persuasive function, which is a distinctive feature of both popularised and non-literary texts – they are supposed to provoke the readers’ thoughts on the relationship between non-linguistic reality and the linguistic way of its interpretation, they also stimulate linguistic interests, which was particularly important in the past when the reflection on the native language was poor.